Pengembangan Permainan Bahasa Berorientasikan Kearifan Lokal Jawa Timur di Sekolah Dasar: Development of Language Games oriented towards East Javanese local wisdom in elementary schools - Damariswara, Rian; Saidah, Karimatus (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this research is to develop language games on grade III material in elementary schools, to know the validity and practicality of language games that have been developed. The development model used is the Borg & Gall development model. The subjects of the study were grade III students at SDN 4 and SDN 1. Data collection techniques were by observation and questionnaire. Data analysis uses descriptive qualitative and quantitative. The results of the study were language games developed as many as 13 games presented in three types of learning stages. Thirteen language games, validated by Indonesian learning experts with a value of 85.8%. These results, that the language game in class III fairy tale material elementary schools was declared very valid and very complete. In addition to validity, practicality is obtained from user or teacher assessments. Both teachers considered that the development of language games could be used with a value of 89.2%.